LABORATORY DIAGNOSTICS OF PANCREATIC DISEASES: CURRENT APPROACHES AND EMERGING BIOMARKERS (International Conference on Educational Discoveries and Humanities, 2025)
The pancreas plays a vital role in both endocrine and exocrine functions, and its dysfunction is associated with a wide range of disorders including acute and chronic pancreatitis, pancreatic cancer, and diabetes mellitus. Early and accurate diagnosis of pancreatic diseases remains a clinical challenge due to overlapping symptoms and nonspecific biochemical markers. This article provides a comprehensive overview of current laboratory diagnostic methods used in the evaluation of pancreatic diseases, including enzymatic assays, immunological tests, and molecular diagnostics. Furthermore, we discuss emerging biomarkers and the potential of omics-based approaches to improve diagnostic accuracy and patient outcomes.